Parallelisierung von Algorithmen zur IR-Luftbildanalyse von Laubholzmischbeständen zur Verifizierung der Ausbreitung von Eichenkomplexschäden - Bülling, Jonas

Price-Based Allocation Games - Koepe, Jörn

Sicherheit von hybriden FPGA-Systemen in der industriellen Automatisierungstechnik -- Anforderungen und Umsetzung - Tölke, Christian

Dynamic OpenCL Task Scheduling for Energy and Performance in a Heterogeneous Environment - Wüllrich, Gunnar

Black-Box Accumulation: Collecting Incentives in a Privacy-Preserving Way - Jager, Tibor; Rupp, Andy (Proceedings on Privacy Enhancing Technologies)

Factors Affecting the Scientific Impact of Literature Reviews: A Scientometric Study - Wagner, Gerit; Prester, Julian; Roche, Maria; Benlian, Alexander; Schryen, Guido (International Conference on Information Systems)

Development of two novel face-recognition CAPTCHAs: a security and usability study - Schryen, Guido; Wagner, Gerit; Schlegel, Alexander (Computers & Security)
CAPTCHAs are challenge-response tests that aim at preventing unwanted machines, including bots, from accessing web services while providing easy access for humans. Recent advances in artificial-intelligence based attacks show that the level of security provided by many state-of-the-art text-based CAPTCHAs is declining. At the same time, techniques for distorting and obscuring the text, which are used to maintain the level of security, make text-based CAPTCHAs diffcult to solve for humans, and thereby further degrade usability. The need for developing alternative types of CAPTCHAs which improve both, the current security and usability levels, has been emphasized by several researchers. With this study, we contribute to research through (1) the development of two new face recognition CAPTCHAs (Farett-Gender and Farett-Gender&Age), (2) the security analysis of both procedures, and (3) the provision of empirical evidence that one of the suggested CAPTCHAs (Farett-Gender) is similar to Google's reCAPTCHA and better than KCAPTCHA concerning effectiveness (error rates), superior to both regarding learnability and satisfaction but not effciency.
Keywords: CAPTCHA; Usability; Facial features; Gender classiffcation; Age classification; Face recognition reverse Turing test

Offshore Metocean Station for Energy Purposes - Balluff, Stefan; Bendfeld, Jörg (Journal of Sustainable Development of Energy, Water and Environment Systems)

Ausbildungsvorbereitung als Domäne - Inklusion in der Exklusion? - Frehe, Petra; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Thermochromic modulation of surface plasmon polaritons in vanadium dioxide nanocomposites - Jostmeier, Thorben; Mangold, Moritz; Zimmer, Johannes; Karl, Helmut; Krenner, Hubert J.; Ruppert, Claudia; Betz, Markus (Optics Express)
We propose and implement a new concept for thermochromic plasmonic elements. It is based on vanadium dioxide (VO2) nanocrystals located in the near field of surface plasmon polaritons supported by an otherwise unstructured gold thin film. When the VO2 undergoes the metal-insulator phase transition, the coupling conditions for conversion of light into propagating surface plasmon polaritons change markedly. In particular, we realize thermochromic plasmonic grating couplers with substantial switching contrast as well as tunable plasmonic couplers in a Kretschmann configuration. The use of VO2 nanocrystals permits highly repetitive switching and room temperature operation. Simulations based on the actual dielectric function of our VO2 nanocrystals agree well with the experiment.

Giant photon bunching, superradiant pulse emission and excitation trapping in quantum-dot nanolasers - Jahnke, Frank; Gies, Christopher; Aßmann, Marc; Bayer, Manfred; Leymann, H. A. M.; Foerster, Alexander; Wiersig, Jan; Schneider, Christian; Kamp, Martin; Höfling, Sven (Nature Communications)
Light is often characterized only by its classical properties, like intensity or coherence. When looking at its quantum properties, described by photon correlations, new information about the state of the matter generating the radiation can be revealed. In particular the difference between independent and entangled emitters, which is at the heart of quantum mechanics, can be made visible in the photon statistics of the emitted light. The well-studied phenomenon of superradiance occurs when quantum–mechanical correlations between the emitters are present. Notwithstanding, superradiance was previously demonstrated only in terms of classical light properties. Here, we provide the missing link between quantum correlations of the active material and photon correlations in the emitted radiation. We use the superradiance of quantum dots in a cavity-quantum electrodynamics laser to show a direct connection between superradiant pulse emission and distinctive changes in the photon correlation function. This directly demonstrates the importance of quantum–mechanical correlations and their transfer between carriers and photons in novel optoelectronic devices.

Ultrasonic transmission measurements in the characterization of viscoelasticity utilizing polymeric waveguides - Bause, Fabian; Rautenberg, Jens; Feldmann, Nadine; Webersen, Manuel; Claes, Leander; Gravenkamp, Hauke; Henning, Bernd (Measurement Science and Technology)
Keywords: material characterization; material parameters; acoustic waveguide; daming; ultrasonic transducer

Determination of the material properties of polymers using laser-generated broadband ultrasound - Claes, Leander; Meyer, Thorsten; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Journal of Sensors and Sensor Systems)

Miniaturized all-optical Sound Pressure Sensor - Fischer, Balthasar; Claes, Leander (INTER-NOISE 2016)

Increasing the Sensitivity of Impedance with Respect to Material Parameters of Triple-Ring Electrode Piezoelectric Transducers using Algorithmic Differentiation - Jurgelucks, Benjamin; Claes, Leander

Optimisation of triple-ring-electrodes on piezoceramic transducers using algorithmic differentiation - Jurgelucks, Benjamin; Claes, Leander (AD2016 The 7th International Conference on Algorithmic Differentiation)

Characterization of Continuous-fiber Reinforced Thermoplastics Using Thermoacoustically Excited Ultrasonic Lamb Waves - Webersen, Manuel; Johannesmann, Sarah; Claes, Leander; Henning, Bernd (2016 IEEE IUS~Proceedings)

Vergleich zweier Verfahren der Unsicherheitsabschätzung bei linearisierten inversen Problemen mittels Bayes’scher Inferenz und Pseudoinverse am Beispiel akustischer Transmissionsmessung - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (Sensoren und Messsysteme 2016)

Uncertainty estimation for linearised inverse problems comparing Bayesian inference and a pseudoinverse approach for acoustic transmission measurements - Feldmann, Nadine; Bause, Fabian; Henning, Bernd (tm - Technisches Messen)

Experteninterviews mit Schulleiterinnen und Schulleitern an rheinland-pfälzischen Schwerpunktschulen – Erste Einblicke in den Prozess der qualitativen Inhaltsanalyse - Scheer, David (Bildungs- und Erziehungsorganisationen im Spannungsfeld von Inklusion und Ökonomisierung)